2010
DOI: 10.4028/www.scientific.net/msf.650.265
|View full text |Cite
|
Sign up to set email alerts
|

Study to Microstructure and Mechanical Properties of Mg Containing High Entropy Alloys

Abstract: In this paper, alloys with compositions of Mgx(MnAlZnCu)100-x (x: atomic percentage; x=20, 33, 43, 45.6 and 50 respectively) were designed by using the strategy of equiatomic ratio and high entropy of mixing. Microstructure and mechanical properties of the new high entropy alloy were studied. The alloys were prepared by induction melting and then were cast in a copper mold in air. The alloy samples were examined by microhardness tester, XRD, SEM, thermal analyzer and testing machine for material strength. Allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…It had a density of 3.91 g cm −3 . Li et al [8,9] studied Mg-containing HEAs. These authors prepared Mg x (MnAlZnCu) 100−x alloys by induction melting and casting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It had a density of 3.91 g cm −3 . Li et al [8,9] studied Mg-containing HEAs. These authors prepared Mg x (MnAlZnCu) 100−x alloys by induction melting and casting.…”
mentioning
confidence: 99%
“…These authors prepared Mg x (MnAlZnCu) 100−x alloys by induction melting and casting. [8] The alloys had multi-phase structures, composed mainly of hcp phases and Al-Mn icosahedral quasicrystalline phases. Depending on the composition, the alloys had densities of 2.20-4.29 g cm −3 .…”
mentioning
confidence: 99%
“…The theoretical criterion for the solid solution structure also predicts the BCC structure for this alloy as VEC = 4.24 (<6.87). Li et al [27] synthesized HEA using Mg with equiatomic AlCuMnZn alloy in different atomic percentage from 20 to 50. It was found that microstructure contains Al-Mn icosahedral phase which was a thermally-stable phase and a HCP phase in Mg 20 (AlCuMnZn) 80 alloy.…”
Section: Mechanical Alloying and Consolidationmentioning
confidence: 99%
“…Sputtering, plasma nitriding, and cladding are the surface modification techniques used to produce thin films and thick layers of HEAs on various substrates. For LWHEA, an addition of low-density metals (Mg, Al, Ti, Be, Sc, and Li) is the criterion for designing, therefore, vacuum arc melting and mechanical alloying followed by sintering are the two main processing techniques that have been used by researchers [22][23][24][25][26][27][28][29].…”
Section: Processing Of Lwheasmentioning
confidence: 99%
See 1 more Smart Citation